Analisis Penerapan Metode Pembelajaran Bahasa Arab Kelas IV - Mubarok, Muslim; Nizam, Mokhammad; Fitriani, Fitriani (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2022)
This article is motivated by learning Arabic for class IV MI Miftahul Ulum Cepokolimo which has problems causing >50% to fail in the UAS. This article aims to describe the application of Arabic learning methods in class IV MI Miftahul Ulum Cepokolimo. This research uses a qualitative research approach with the type of case study research. With data sources from teachers, students, and the learning process. Collecting data through interviews, observation, and documentation. Data is collected, reduced, presented, and then concluded. The results showed that the Arabic language learning process only applied two learning methods, namely grammar translation and audiolingual with a ratio of >75%: <25%. The selection of learning methods is not in accordance with the competencies to be achieved. Learning Arabic uses limited methods and media, so the result is that students are less motivated in the learning process. The application of learning methods that are less systematic and thorough. Evaluation of learning at the end of the meeting is not always carried out.